Preclinical evaluation of reversible pulsed electrical field: electrophysiological and histological assessment of myocardium - Zhai, Zongwang; Ling, Yuchen; Wang, Yanjiang; Shi, Liang; Liu, Xingpeng (Frontiers in Cardiovascular Medicine, 2024)
Background: Pulsed field ablation (PFA), as a non-thermal ablation modality, has received increasing attention. To explore whether reversible pulsed electric fields (RPEF) can temporarily inhibit electrical conduction and provide a novel method for precise ablation of arrhythmia. Methods: RPEF energy was delivered from a tip catheter to the atrium of 6 dogs, followed by a series of electrogram and histology assessments. Results: RPEF ablation of ordinary myocardium resulted in an average reduction of 68.3% (range, 53.7% to 83.8%) in electrogram amplitude, while 5 min later, the amplitude in 8 EKGs returned to 77.9% (range, 72.4% to 87.3%) of baseline. Similarly, the amplitude of the sinoatrial node reduced by an average of 73.0% (range, 60.2% to 84.4%) after RPEF ablation, but recovered to 84.9% (range, 80.3% to 88.5%) of baseline by 5 min. No necrotic change was detected in histopathology. Transient third-degree atrioventricular block occurred following the ablation of the maximum His potential sites with RPEF, the duration of which was voltage dependent. Histopathological results showed necrosis of the myocardium at the ablation sites but no injury to His bundle cells. Conclusions: RPEF can be applied to transiently block electrical conduction in myocardial tissues contributing to precise ablation.